At the Edges of Sleep Moving Images and Somnolent Spectators - Ma, Jean (University of California Press, 2022)
At the Edges of Sleep considers sleep in film and moving image art as both a subject matter to explore onscreen and a state to induce in the audience. Far from negating action or meaning, sleep extends into new territories as it designates ways of existing in the world, in relation to people, places, and the past. Defined positively, sleep also expands our understanding of reception beyond the binary of concentration and distraction. These possibilities converge in the work of Thai filmmaker and artist Apichatpong Weerasethakul, who has explored the subject of sleep systematically throughout his career. In examining Apichatpong's work, Jean Ma brings together an array of interlocutors-from Freud to Proust, George Méliès to Tsai Ming-liang, Weegee to Warhol-to rethink moving images through the lens of sleep. Ma exposes an affinity between cinema, spectatorship, and sleep that dates to the earliest years of filmmaking, and sheds light upon the shifting cultural valences of sleep in the present moment. "Moving with ease across historical contextualization, theoretical inquiry, and the close reading of films and other cultural objects, Jean Ma takes on urgent contemporary debates pertaining to corporeality, slowness, attention, and cinematic relocation. A true pleasure to read." - ERIKA BALSOM, author of After Uniqueness: A History of Film and Video Art in Circulation "Intellectually ambitious, erudite across a number of fields, poetically written yet lucid, and both historically informed and deeply attuned to our own moment." - KAREN REDROBE, author of Crash: Cinema and the Politics of Speed and Stasis "Downright groundbreaking in its far-ranging and far-reaching insights." - DANA POLAN, Cinema Studies, New York University